Digitalization of the Economy and the Cultural Impact of Consumption in Modern Society: A Review from Al-Syaibanī’s Perspective - Syamsuri Syamsuri; Maulana Farizi; Husnul Khotimah (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2022)
This study investigated the role of economic digitalization in increasing consumerism in modern society. Consumption issues have arisen along with the prevalence of digital advancement. Despite this trend, modern society continues to impose consumption limits based on one's income or possessions. Thus, this research will answer the consumption issues under the Islamic view according to Imam Al-Syaibani. This study is a descriptive-explanatory qualitative approach to examine consumerism in the context of economic digitalization. To that end, researchers conducted a review of relevant written materials to elucidate contemporary society's consumption issues, which stem from the current trend of digital economy sophistication. The study findings indicate that the prevalence of the digital economy in modern society engenders consumption patterns that impede social welfare, owing to its promotional services, support systems, and lenient credit policies. This is contrary to Islamic principles, as the consumption aspect is based on the benefit of maqashid Al-syariah. Imam Al-Syaibani is one of the economic leaders who has spoken about consumption. Al-Kasb Book discusses the hierarchy of consumption namely Fardl ‘āyn, Mandūb, and Mūba. To reflect, it is possible to address the social problem in modern society using the concept presented.